Changes in the somatic cells counts and total bacterial counts in raw goat milk during lactation and their relationships to selected milk traits - Jan Kuchtík (Italian Journal of Animal Science, 2021)
The main aim of our study was to assess changes in the somatic cell count (SCC) and total bacterial count (TBC) in the raw milk of White Short-haired (WSH) goats (n = 13) during lactation and their relationships to daily milk yield (DMY), basic milk components, the acidity of milk and California mastitis test (CMT). All monitored goats were in the second lactation and throughout the study, all these goats were clinically healthy. Individual milk recording and sampling of each goat during lactation were carried, from the end of April to October on the mean 54, 89, 124, 159, 194 and 229 day of lactation and all monitored goats were milked by hand. Throughout lactation, the mean values of Log SCC ranged from 5.60 to 5.91 and the mean values of Log TBC from 2.85 to 3.58, whilst the SL had no significant effect on any of these traits. The Log SCC had a significant positive correlation (p ≤ .01) only with CMT, which suggests that CMT may be a good predictor of the SCC. On the other hand, all correlations of Log TBC with all other traits were insignificant. Regarding the effect of the SL on all other monitored traits, it had a highly significant effect (p ≤ .01) on the DMY, contents of fat and total protein and titratable acidity. The SL had also a significant effect (p ≤ .05) on the pH. Nevertheless, the SL had no significant effect on lactose content and CMT. The results of our study suggest that in clinically healthy WSH goats, the SCCs in goat milk after milking should only rarely be higher than 1,000,000 cells/mL and if strict milking hygiene is applied, the TBCs should be significantly lower than 500,000 cfu/mL. The present study also suggests that the SCCs in milk in WSH goats are comparable to their counts in most other breeds.HIGHLIGHTS The stage of lactation had no significant effect on the SCC and TBC. In clinically healthy WSH goats, the SCCs in raw milk should rarely be higher than 1,000,000 cells/mL. When strict milking hygiene is applied in clinically healthy goats, the TBCs in milk after milking should be significantly lower than 500,000 cfu/mL.